2022
DOI: 10.1007/s11606-021-07210-9
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perspectives on Improving Patient-Provider Relationships and Provider Communication During Opioid Tapering

Abstract: Background Efforts to reduce opioid overdose fatalities have resulted in tapering (i.e., reducing or discontinuing) opioid prescriptions despite a limited understanding of patients’ experiences. Objective To explore patients’ perspectives on opioid taper experiences to ultimately improve taper processes and outcomes. Design Qualitative study. Participants Patients on long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Similar to other studies, 8,12,31 many of the limitations reported by STORM program patients related to a need for additional resources to treat pain or tapering adverse effects. Nearly half of patients expressed frustration with nonpharmacological pain management suggestions provided by pharmacists; patients found these suggestions redundant to options they had already tried or unaffordable.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Similar to other studies, 8,12,31 many of the limitations reported by STORM program patients related to a need for additional resources to treat pain or tapering adverse effects. Nearly half of patients expressed frustration with nonpharmacological pain management suggestions provided by pharmacists; patients found these suggestions redundant to options they had already tried or unaffordable.…”
Section: Discussionsupporting
confidence: 61%
“…Our findings reiterate past findings of the importance of provider empathy with patient experiences, mentally preparing patients for tapering, and individualizing tapering plans. 8,12,31 The incorporation of these elements facilitated the success of the STORM program, and based on findings from our study, additional program elements in line with these themes could be key to improving STORM and designing new programs.…”
Section: Science and Practicementioning
confidence: 67%
See 2 more Smart Citations
“…9,10,11 Frequent visits (at least monthly but often weekly if there are comorbid mental health conditions) with the physician and behavioral health team are recommended during a taper. 12 At these visits progress and patient experience are reviewed, risks and benefits are evaluated, and adjustments are made to the plan. It is often appropriate to "pause" a taper while a patient adjusts to their new dose.…”
Section: Patient Buy-inmentioning
confidence: 99%